Assessment of diabetic patients’ adherence of described treatment - Abdul-Jabbar kuriet, Fatima (Latakia University Journal -Medical Sciences Series, 2019)
Diabetes is a global health problem Affect society and its members; It leads to increased mortality and morbidity in many countries of the world. The patient can avoid many diseases by adhering to the proper hygiene rules in eating, drinking and sports. The study was conducted on a sample of 300 diabetic patients of both sexes and reviewed the Diabetes Center at the National Hospital in Lattakia province, using a tool provided by the researcher based on the relevant references. The results of the research showed that most patients are committed to checking blood sugar and exercise, fast or slow walking . also, About half of the patients follow the diet and exercise. The study also showed that patients eat more potatoes, rice and desserts, and that most of fruits eaten are apples and oranges, while the most carbohydrates were potatoes and bread. The study recommended the intensification of educational programs for diabetics to introduce them to the importance of healthy food and exercise and re-search for a larger sample, including other types of foods and sports in addition to conducting a comparative study on the incidence of complications with non-commitment to diet and sports. يعد الداء السكري مشكلة صحية عالمية تؤثر على المجتمع وأفراده, ويؤدي إلى زيادة معدل الوفيات والإمراضات في العديد من بلدان العالم, ويمكن للمريض أن يتفادى الكثير من الأمراض بالتزامه بالقواعد الصحية المناسبة في الأكل والشرب واتباع الرياضة. هدف هذا البحث إلى تقييم مدى التزام مرضى الداء السكري بالعلاج الموصوف, أجري البحث على عينة قوامها 300 مريض سكري من كلا الجنسين راجعو مركز الداء السكري في المشفى الوطني في محافظة اللاذقية , باستخدام أداة طورها الباحث اعتمادا على المراجع المتعلقة بموضوع البحث وأظهرت نتائج البحث أن معظم المرضى كانوا ملتزمين بفحص نسبة السكر في الدم , يمارسون رياضة المشي السريع أو البطيء وكان حوالي نصف المرضى يتبعون الحمية الغذائية وممارسة الرياضة . أظهر البحث ايضا ان المرضى يكثرون من تناول البطاطا والرز والحلويات, وأن أكثر الفواكه المتناولة هي التفاح والبرتقال . أما أكثر الكربوهيدرات المتناولة فكانت البطاطا والخبز. أوصت الدراسة بتكثيف البرامج التثقيفية لمرضى الداء السكري لتعريفهم بأهمية الغذاء الصحي وممارسة الرياضة واعادة البحث على عينة اكبر وتشمل أنواع أخرى من الأغذية وممارسة رياضات أخرى بالإضافة إلى إجراء دراسة مقارنة حول معدل حدوث المضاعفات مع عدم الالتزام بالحمية والرياضة.